Um estudo comparativo sobre o uso dos pronomes este e esse nas gramáticas normativas e pedagógicas do Português - Pereira, Karla Giselly Melo de Maria (2018)
The study of demonstrative pronouns of Brazilian Portuguese generates a bit of doubt, will I use este or esse?. This question follows the study of the demonstratives from Vulgar Latin, a period in which there was a linguistic transition, in which we have the substitution of hic, haec, hoc for ĭste, ĭsta, ĭstud, to refer to the first person of speech, In classical Latin, it was used both for the first person and the second person of the speech, and it is used the identity pronouns ĭpse, ĭpsa, ĭpsum to take the place of ĭste, and thus refer to the 2nd Speech. This first change in the system of use of statements and others that have occurred throughout history, may have generated this doubt in use. In the present study, the aim of this research was to analyze the history of grammar in order to compare the normative grammars of Almeida (2009), of Cunha and Cintra (2013), of Rocha Lima (2014) and of Bechara (2015), and the pedagogical ones of Perini (2010), of Neves (2011), of Castilho and Elias (2012), and of Bagno (2012), on the use of the statements, and later, Demonstratives in classic texts and current texts. For the constitution of this corpus, we chose 5 short stories by Machado de Assis and articles published from January to June 2015 by journalist Ruth de Aquino for Época Magazine. Our results indicate that there is a certain disagreement, between normative and pedagogical grammars, regarding the use of este and esse statements, in the references related to the discourse. We also observe that in normative grammars, there is a certain "relativization" in the use of statements. We analyzed 292 demonstrative records and the textual analyzes indicated este in the anaphoric references in the classic texts the latter is predominant, and in the current texts we have the predominance of the esse.